God loves everyone ”with the same love He has for the entire world“. Incursio patristica - Liviu Petcu (Anastasis: Research in Medieval Culture and Art, 2018)
In this article, we intend to highlight, as much as possible in a limited number of words and using the texts of the Holy Fathers of the Church, the multifaceted revelation of God’s love for us, specifically: through the entire Creation, through His Son’s unfathomable Incarnation through which He makes evident the true value of man, through His Cross which is the key to the mystery of Christ’s love, through His Resurrection and Ascension, by indwelling us with the Holy Spirit, by giving Himself for and to us as only He Himself could in the Holy Eucharist, through the fact that God always intends the best for man in all His actions and loves each of us to the fullest, etc. Moreover, we have emphasized the fact that the multitude of man’s sins does not exceed God’s love for us. This, of course, should not be understood as an exhortation to continue in sin, because God is merciful and forgives man, but it should be regarded as an exhortation to repent sincerely. God always awaits for the sinner to return to Him, through repentance, to bestow upon him forgiveness and, simultaneously, peace, joy, serenity and eternal blessing. Each page of this article is intended as an invitation to love, and to grow in that love of God and our neighbours.